Assessing the quality of economic evaluations of clinical nurse specialists and nurse practitioners: A systematic review of cost-effectiveness. (2015) - Marshall, Deborah A.; Donald, Faith; Lacny, Sarah; Reid, Kim; Bryant-Lukosius, Denise; Carter, Nancy; Charbonneau-Smith, Renee; Harbman, Patricia; Kaasalainen, Sharon; Kilpatrick, Kelley; Martin-Misener, Ruth; DiCenso, Alba
Abstract: A limited number of randomized controlled trials (RCTs) including economic analysis have supported the cost-effectiveness of nurse practitioners and clinical nurse specialists delivering care in a variety of settings. Our objective was to examine the quality of economic evaluations in this body of literature using the Quality of Health Economic Studies (QHES) tool, and highlight which questions of the quality assessment tool are being addressed adequately or require further attention within this body of literature. Of 43 RCTs included in our systematic review, the majority (77%) fell in the poor study quality quartile with an average total QHES score of 39 (out of 100). Only three studies (7%) were evaluated as high quality. Inter-rater agreement (prior to consensus process) was high (83% agreement). Four criteria for the quality of economic evaluations were consistently addressed: specification of clear, measurable objectives; pre-specification of subgroups for subgroup analyses; justified conclusions based on study results; and disclosure of study funding source. A clear statement of the primary outcome measures, incremental analysis, and assessment of uncertainty were often unclear or missing. Due to poor methodological quality, we currently lack a solid evidence base to draw clear conclusions about the cost-effectiveness of nurse practitioners and clinical nurse specialists. Higher quality economic evaluations are required to inform these questions.